Metal polar plate electrode material for all-vanadium redox flow battery and preparation method of metal polar plate electrode material
By using titanium plates as metal substrates in all vanadium liquid flow batteries and forming an interface bonding layer and corrosion resistance layer through vapor deposition technology, the problem of insufficient conductivity and corrosion resistance of the electrode plates in the prior art is solved, and the problem of insufficient conductivity and corrosion resistance of the electrode plates is realized Stable operation and long-term use in high potential environments.
Patent Information
- Application Number
- CN202411660398.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-14
AI Technical Summary
The conductive and mechanical strength of graphite or carbon material plates in existing all-vanadium liquid flow batteries is insufficient, making it difficult to maintain stability in high potential environments, and conventional metal plates are prone to corrosion in acidic electrolytes, making it difficult to meet long-term stable operation. Require.
Using industrial pure titanium plates with uniform thickness as metal substrates to form nano-level interface bonding layer and surface corrosion-resistant layer. Metal materials such as Ti, Ta, Nb, Pt are deposited through vapor deposition technology to form a dense corrosion-resistant layer to improve Corrosion resistance and conductivity of the electrode plate.
It realizes long-term stable operation in the all-vana liquid-flow battery electrolyte, reduces contact resistance, improves the energy efficiency of the battery, significantly improves the corrosion resistance and conductivity of the electrode plates, and extends the service life of the battery.
Smart Images

Figure CN119315048A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a metal plate electrode material for an all-vanadium liquid flow battery and a preparation method thereof. Background Art
[0002] As a common energy storage method, lithium-ion batteries have high energy density and relatively acceptable prices, and have been widely used in mobile phones, electric vehicles and other fields. However, lithium-ion batteries have poor performance in terms of safety and long-term durability. In comparison, flow batteries are safer and have a longer service life, making them a favorable competitor to lithium-ion batteries.
[0003] Liquid flow batteries mainly store energy in flowing liquid electrolytes. The most common liquid flow battery currently is the all-vanadium liquid flow battery. Taking it as an example, the entire battery includes two reversible electrode half reactions. During charging, tetravalent vanadium (VO 2+ ) and trivalent vanadium (V 3+ ) form pentavalent vanadium (VO2 + ) and divalent vanadium (V 2+ ), and during discharge, the reverse process occurs to reform tetravalent vanadium and trivalent vanadium. During the whole process, only the vanadium ions in the solution undergo valence changes, and no additional solids or gases participate in the reaction or generation. Therefore, the entire battery can remain relatively stable during long-term charge and discharge cycles.
[0004] Typical all-vanadium flow battery devices such as Figure 1 As shown, the pump group 6 transports the electrolyte in the electrolyte storage tank 1 to the electrolyte chamber 5 in the battery stack through the pipeline 2, and is separated by the proton membrane 4, with battery electrodes 3 at both ends, and the battery electrodes are connected to the external power supply / load 7 for charging and discharging. The electrolyte used in the all-vanadium liquid flow battery is generally a mixed solution formed by more than 1 mol / L sulfuric acid and more than 1 mol / L vanadium salt. The electrolyte is very corrosive, and the battery plate is in contact with the electrolyte for a long time, and there are effects such as applied potential. In order to maintain battery performance, the battery plate needs to remain stable in the system for a long time without being corroded, while maintaining good conductivity.
[0005] In the prior art, patent document CN202311602405.8 discloses a method for preparing a composite bipolar plate for a liquid flow battery based on a graphene network, which uses a pressurized dissolved gas method combined with a bubble soft template to prepare a wet graphene oxide foam, and then freeze-dries and pyrolyzes the wet graphene oxide foam to prepare a reduced three-dimensional graphene foam; the graphene foam is compressed, vacuum impregnated with a resin solution, and rolled and cured to obtain a composite bipolar plate for a liquid flow battery, which has excellent electrical conductivity and mechanical strength. Patent document CN201811342099.8 discloses a metal composite bipolar plate for an all-vanadium liquid flow battery and a preparation method thereof. The metal composite bipolar plate consists of a metal main structure and a surface anti-corrosion functional layer, which is combined into an organic whole through processes such as thermal spraying, cold spraying, high-temperature pressing and coating, showing extremely high electronic conductivity, while also having good strength, corrosion resistance and processability. However, the prior art still has the following defects: (1) At present, the all-vanadium liquid flow battery system mainly uses graphite or carbon-plastic composite plates. These carbon-based electrode materials have poor conductivity and mechanical processing performance. In addition, since carbon materials cannot withstand high potential in the positive electrode environment, a slightly higher potential will greatly accelerate the oxidation and dissolution of carbon materials. Long-term use will lead to performance degradation and potential safety issues.
[0006] (2) Conventional metal plates are difficult to maintain long-term stability in the electrolyte of all-vanadium flow batteries. For example, the passivation film formed on the surface of common stainless steel materials under the acidic conditions of flow batteries is difficult to protect the stability of the material inside, and further dissolves and corrodes the substrate. In addition, the metal or organic polymer coatings prepared by thermal spraying, coating and other methods have poor conductivity and corrosion resistance, and are difficult to meet the current long-term stable operation requirements of flow batteries in years.
[0007] Therefore, it is particularly important to develop a coating based on metal plates suitable for all-vanadium liquid flow battery systems to protect against electrolyte corrosion. Summary of the invention
[0008] The main purpose of the present invention is to provide a metal plate electrode material for an all-vanadium liquid flow battery, which has the advantages of resisting corrosion from the electrolyte of the all-vanadium liquid flow battery, maintaining stable resistance under high positive potential conditions, and having long-term chemical stability and excellent conductivity.
[0009] Another object of the present invention is to provide a method for preparing the metal plate electrode material, which has a simple process and is easy to industrialize.
[0010] To achieve the above object, the present invention is implemented through the following technical solutions: The present invention provides a metal plate electrode material for an all-vanadium liquid flow battery, comprising a metal substrate, an interface bonding layer and a surface corrosion resistant layer, wherein: The metal substrate is an industrial pure titanium plate with uniform thickness; The component of the interface bonding layer is selected from Ti, Ta, Nb, TiO x 、NbO x 、TaO x One or more of; The component of the surface corrosion-resistant layer is selected from one or more of Pt, Ru and Ir.
[0011] The present invention also provides a method for preparing a metal plate electrode material for an all-vanadium liquid flow battery, comprising the following steps: (1) An industrial pure titanium plate with uniform thickness was selected as a metal substrate, which was ultrasonically cleaned in ethanol and water in turn to remove grease and debris on the surface; (2) fixing the metal substrate treated in step (1) on a rack, moving it into a closed reaction chamber and evacuating it to 0.1-0.3 Pa, heating it to 300-500° C. and keeping it warm for 20-40 minutes; introducing Ar gas or a mixed gas of Ar and O2 into the closed reaction chamber through the gas path and the air hole, and then controlling the vacuum degree to 0.4-0.6 Pa, and vapor-depositing a first metal target material on the surface of the metal substrate to form an interface bonding layer under the condition of a deposition current of 0.8-1.5 A, and the deposition time is 10-20 minutes; (3) Fixing the metal substrate containing the interface bonding layer in step (2) onto a rack, moving it into a closed reaction chamber and evacuating it to 0.1-0.3 Pa, heating it to 300-500° C. and keeping it warm for 20-40 minutes; then introducing Ar gas into the closed reaction chamber through the gas path and the air hole, controlling the vacuum degree to 0.4-0.6 Pa, and vapor-depositing a second metal target material on the surface of the interface bonding layer to form a surface corrosion-resistant layer under the condition of a deposition current of 0.1-1 A, and the deposition time is 5-10 minutes, thereby obtaining the product.
[0012] Preferably, in step (2), the volume ratio of Ar to O2 in the Ar and O2 mixed gas is 5:1.
[0013] Preferably, in step (2), the first metal target is selected from one or more of Ti, Ta, and Nb.
[0014] Preferably, in step (2), the composition of the interface bonding layer is selected from Ti, Ta, Nb, TiO x 、NbO x 、TaO x One or more of .
[0015] Preferably, in step (3), the component of the surface corrosion-resistant layer is selected from one or more of Pt, Ru, and Ir.
[0016] Preferably, in step (3), the second metal target is selected from one or more of Pt, Ru, and Ir.
[0017] Preferably, in steps (2) and (3), the mixture is heated to 400° C. and kept warm for 30 minutes.
[0018] Preferably, in steps (2) and (3), the vapor deposition method is magnetron sputtering or multi-arc ion plating.
[0019] The present invention also provides a metal plate for an all-vanadium liquid flow battery, comprising the metal plate electrode material.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The metal plate electrode material of the present invention uses titanium as the metal substrate, and has good corrosion resistance, electrical conductivity and easy processing; the surface corrosion-resistant coating plays a corrosion-resistant role in the electrolyte of the all-vanadium liquid flow battery, ensures the stability of the metal plate, and can also reduce the contact resistance and improve the energy efficiency of the battery; the interface bonding layer can further improve the bonding performance between the surface corrosion-resistant layer and the titanium substrate, and also avoid the surface defects of the titanium substrate itself affecting the density of the metal corrosion-resistant layer.
[0021] (2) The present invention uses a vapor deposition method to plate a dense, nano-level thick corrosion-resistant metal such as Pt on a titanium substrate. As a metal plate electrode material, it can operate for a long time in the electrolyte of an all-vanadium liquid flow battery and remain stable, thereby improving the battery efficiency of the liquid flow battery. Compared with graphite plates, it is more convenient to machine. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the structure of the all-vanadium liquid flow battery in the prior art, wherein: 1. electrolyte storage tank; 2. pipeline; 3. battery electrode; 4. proton membrane; 5. electrolyte chamber; 6. pump group; 7. power supply / load.
[0023] Figure 2 Schematic diagram of the structure of the metal plate electrode material used for the all-vanadium liquid flow battery in the embodiment, 101, metal substrate; 102, interface bonding layer; 103, surface corrosion resistant layer. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0025] Example 1 (1) Select industrial pure titanium with uniform thickness as the plate substrate, and ultrasonically clean the pure titanium in ethanol and water to remove surface grease and surface debris.
[0026] (2) Fix the sample obtained in step (1) on a rack, move it to a closed reaction chamber and evacuate the interior thereof. When the vacuum is evacuated to 0.1 Pa, heat it to 400° C. through a heater and keep it warm for 30 minutes. Then, introduce Ar gas into the chamber through the gas path and the air hole, control the vacuum degree of the process to 0.5 Pa through the exhaust system, control the Pt target deposition current to 0.5 A, and the deposition time to 10 min, to obtain a titanium plate with a corrosion-resistant Pt coating.
[0027] Example 2 (1) Select industrial pure titanium with uniform thickness as the plate substrate, and ultrasonically clean the pure titanium in ethanol and water to remove surface grease and surface debris.
[0028] (2) The sample obtained in step (1) is fixed on a rack, moved to a closed reaction chamber and the inside is evacuated. When the vacuum is evacuated to 0.1 Pa, it is heated to 400°C by a heater and kept warm for 30 minutes. Then, Ar and O2 gases are introduced into the chamber through the gas path and the air hole, with a volume ratio of 5:1. The vacuum degree of the process is controlled to be 0.5 Pa by the exhaust system, the Ti target deposition current is controlled to be 1A, and the deposition time is 10 minutes to obtain a titanium plate coated with an oxide interface bonding layer.
[0029] (3) Fix the sample obtained in step (2) on a rack, move it to a closed reaction chamber and evacuate the interior thereof. When the vacuum is evacuated to 0.1 Pa, start the heater and heat it to 400°C and keep it warm for 30 minutes. Then, introduce Ar gas into the chamber through the gas path and the air hole, control the vacuum degree of the process to 0.5 Pa through the exhaust system, control the Pt target deposition current to 0.5 A, and the deposition time to 5 min to obtain a titanium plate with an oxide interface bonding layer and a corrosion-resistant Pt coating, the structure of which is as follows: Figure 2 shown.
[0030] Example 3 (1) Select industrial pure titanium with uniform thickness as the plate substrate, and ultrasonically clean the pure titanium in ethanol and water to remove surface grease and surface debris.
[0031] (2) The sample obtained in step (1) is fixed on a rack, moved to a closed reaction chamber and the inside thereof is evacuated. When the vacuum is evacuated to 0.1 Pa, it is heated to 400° C. by a heater and kept warm for 30 minutes. Then, Ar gas is introduced into the chamber through the gas path and the air hole, and the vacuum degree of the process is controlled to be 0.5 Pa by the exhaust system, and the Ti target deposition current is controlled to be 1 A, and the deposition time is 10 min to obtain a titanium plate coated with a metal interface bonding layer.
[0032] (3) Fix the sample obtained in step (2) on a rack, move it to a closed reaction chamber and evacuate the interior thereof. When the vacuum is evacuated to 0.1 Pa, start the heater to heat to 400° C. and keep the temperature for 30 minutes. Then, introduce Ar gas into the chamber through the gas path and the air hole, control the vacuum degree of the process to 0.5 Pa through the exhaust system, control the Pt target deposition current to 0.5 A, and the deposition time to 5 min to obtain a titanium plate having a metal interface bonding layer and a corrosion-resistant Pt coating.
[0033] The performance of the samples prepared in the above embodiments was evaluated, and it was found through testing that the conductivity of the above metal plate was about 25000 S / cm, which was about 20 times that of the hard graphite plate.
[0034] The metal plate and commercial carbon-plastic composite plate prepared in Example 2 were used as different positive electrodes, and the negative electrodes were fixed with hard graphite plates to assemble into a single cell. The initial performance after 5 1.0-1.55V charge and discharge cycles is shown in Table 1. It can be seen that the use of metal plates can effectively improve the voltage efficiency of the all-vanadium liquid flow battery and improve the overall performance of the battery. After a total of 250 cycles, the sample still maintained good stability after operation and can continue to be used.
[0035] Table 1
[0036] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A metal plate electrode material for an all-vanadium liquid flow battery, characterized in that: It includes a metal substrate, an interface bonding layer and a surface corrosion resistant layer, wherein: The metal substrate is an industrial pure titanium plate with uniform thickness; The component of the interface bonding layer is selected from Ti, Ta, Nb, TiO x 、NbO x 、TaO x One or more of; The component of the surface corrosion-resistant layer is selected from one or more of Pt, Ru and Ir.
2. The method for preparing the metal plate electrode material according to claim 1, characterized in that: The following steps are involved: (1) An industrial pure titanium plate with uniform thickness was selected as a metal substrate, which was ultrasonically cleaned in ethanol and water in turn to remove grease and debris on the surface; (2) fixing the metal substrate treated in step (1) onto a rack, moving it into a closed reaction chamber and evacuating it to 0.1-0.3 Pa, heating it to 300-500° C. and keeping it warm for 20-40 minutes; introducing Ar gas or a mixed gas of Ar and O2 into the closed reaction chamber through the gas path and the air hole, and then controlling the vacuum degree to 0.4-0.6 Pa, and vapor-depositing a first metal target material on the surface of the metal substrate to form an interface bonding layer under the condition of a deposition current of 0.8-1.5 A, and the deposition time is 10-20 minutes; (3) Fixing the metal substrate containing the interface bonding layer in step (2) onto a rack, moving it into a closed reaction chamber and evacuating it to 0.1-0.3 Pa, heating it to 300-500° C. and keeping it warm for 20-40 minutes; then introducing Ar gas into the closed reaction chamber through the gas path and the air hole, controlling the vacuum degree to 0.4-0.6 Pa, and vapor-depositing a second metal target material on the surface of the interface bonding layer to form a surface corrosion-resistant layer under the condition of a deposition current of 0.1-1 A, and the deposition time is 5-10 minutes, thereby obtaining the product.
3. The method for preparing the metal plate electrode material according to claim 2, characterized in that: In step (2), the volume ratio of Ar to O2 in the Ar and O2 mixed gas is 5:
1.
4. The method for preparing the metal plate electrode material according to claim 2, characterized in that: In step (2), the first metal target is selected from one or more of Ti, Ta, and Nb.
5. The method for preparing the metal plate electrode material according to claim 2, characterized in that: In step (3), the second metal target is selected from one or more of Pt, Ru, and Ir.
6. The method for preparing the metal plate electrode material according to claim 2, characterized in that: The composition of the interface bonding layer is selected from Ti, Ta, Nb, TiO x 、NbO x 、TaO x One or more of .
7. The method for preparing the metal plate electrode material according to claim 2, characterized in that: The component of the surface corrosion-resistant layer is selected from one or more of Pt, Ru and Ir.
8. The method for preparing the metal plate electrode material according to claim 2, characterized in that: In steps (2) and (3), heat to 400°C and keep warm for 30 minutes.
9. The method for preparing the metal plate electrode material according to claim 2, characterized in that: In steps (2) and (3), the vapor deposition method is magnetron sputtering or multi-arc ion plating.
10. A metal plate for an all-vanadium liquid flow battery, characterized in that: It comprises the metal plate electrode material as claimed in claim 1.
Citation Information
Patent Citations
Metal compound bipolar plate for all-vanadium redox flow battery and preparation method of metal compound bipolar plate
CN109524682A
A method for preparing a composite bipolar plate for a flow battery based on a graphene network
CN117317278B